THE CORRELATION BETWEEN READING ATTITUDE AND WRITING ACHIEVEMENT OF THE ELEVENTH GRADE STUDENTS OF SMA MUHAMMADIYAH 6 PALEMBANG - Ayu Lestari; Muhammad Holandiyah (State Islamic University of Raden Fatah Palembang, South Sumatra, Indonesia, 2016)
This research was aimed at investigating if there was a correlation between reading attitude and writing achievement of the eleventh grade students of SMA Muhammadiyah 6 Palembang. The writer used correlational research method to find out the relationship between students’ reading attitude and writing achievement. One hundred and ten students participated in this research with the age ranged from 15-17 years old. The writer used ready-made questionnaire used by Tullock-Rhody, Regina and Alexander, J Estill, 1980 and writing test to collect the data. The result of the test were analyzed by using Pearson Product Moment through SPSS (Statistical Package for Social and Science) 16.0. Meanwhile, to measure the correlation between the students’ reading attitude and their writing achievement, it was also referred to the interval coefficient for interpreting the correlation coefficient. From the analysis, it was showed that there was correlation between the two variables since the score of significance .701 higher 0.199 . The factors that influenced this conditions were; 1) most of students spent their time in the library in order to get information, 2) students were interested to read academic and non academic books, 3) more students involved in reading and writing activity.